IMPLEMENTASI MANAJEMEN KURIKULUM DALAM MENINGKATAN MUTU PENDIDIKAN DI SMP PGRI 1 PULAUPANGGUNG, KABUPATEN TANGGAMUS - Apriyani, Mega Apriyani; Purwanti, Eri; Mursyid, Adhar Al (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2018)
AbstractThis research is used to study Learning Curriculum Management in Improving Education Quality in SMP PGRI 1 Pulaupanggung, describing the implementation of management learning curriculum in order to improve the quality of education in SMP PGRI 1 Pulaupanggung, Tanggamus District.The results show that a) .The curriculum planning at SMP PGRI 1 Pulaupanggung is based on the previous evaluation results and the planning of future targets and programs compiled by the principal with all subordinate staff. b) .The organizing of the curriculum includes dividing the teaching tasks for teachers according to their respective areas of expertise, striving for teachers to teach 5 days a week, schedule remedial activities, conduct lessons and try out, schedule an extra curricular curriculum, teaching for teachers about science and technology, and arranging a schedule of teacher meetings in turns. c) .The curriculum implementation includes early learning activities, learning methods, learning media, end activities of learning. d). The curriculum evaluation is using the form of evaluation of cognitive aspects, affective aspects and psychomotor aspects.